PERUBAHAN STATUS HARA NITROGEN PADA AIR GAMBUT DAN GAMBUT BEKAS TERBAKAR AKIBAT PERBEDAAN MUKA AIR: Siahaan, M.1), Yulianti, N.1*), dan Widiastuti, L - Admin journal (AgriPeat, 2017)
The burned peat in the farmland, Kalampangan Village have changed quite dramatically, such the water level is inundated during the rainy season and very dry during the drought season. Such conditions could be affecting the process of decomposition and chemical properties of peat and peat water associated with the availability of nutrients, especially nitrogen. This study aims to determine how the effect of water levels on the status of N in the burned ombrogenic peat in the Kalampangan Village. This research was uses a method of incubation as long as 40 days with the hanging column with the differences of water levels are 0, -10, -20, -30, 10, 20, and 30 cm. Parameter chemical properties of peat and peat, namely pH, total N, organic C, ammonium, ammonia, nitrite and nitrate. Analysis of data of the chemical properties of peat and peat water was done by using ANOVA level of 5% and 1%, then also regression and correlation analysis. The results have showed that there was no significant effect on the chemical properties of water and peat due to the changes in water level. Incubated peats have a very acidic pH with a high positive correlation at drying and a low positive correlation at inundation, while the peat water was indicates a perfect positive correlation at drying and high negative correlation at inundation. Peat showed a high total N with a low positive correlation at drying and a perfect negative correlation at inundation, while the peat water was indicates a perfect positive correlation at drying and a high negative correlation at inundation. Ammonification and nitrification processes were occurring that indicated by the accumulation of NH4 + and NO3 in peat and peat NO3 dissolved in water, where were the results of the regression analysis contained pattern polynomial equations and linear patterns. The equation can be used to predict the concentrations of all three parameters due to the changes in peat water level in Central Kalimantan